Escape dynamics in moderately damped Josephson junctions (Review Article) - Massarotti, D.; Longobardi, L.; Galletti, L.; Stornaiuolo, D.; Montemurro, D.; Pepe, G.; Rotoli, G.; Barone, A.; Tafuri, F. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2012)
The Josephson effect is a privileged access to the macroscopic quantum nature of superconductors. We reviewsome ideas and experimental techniques on macroscopic quantum decay phenomena occurring in Josephson structures. The attention is mainly addressed to intermediate levels of dissipation which characterize a largemajority of low critical current Josephson devices and are therefore an avoidable consequence of nanotechnology applied more and more to Josephson devices. Phase diffusion phenomena take over thermal activation in some temperature ranges also affecting the transition to macroscopic quantum tunneling, enriching the phase diagram mostly defined by the Josephson energy, the temperature and the level of dissipation.